Characterising natural ventilation through open windows in the presence of wind: a theoretical and experimental investigation into the interaction between window geometry and environmental forces, and its application to envelope flow models of natural ventilation - Sharpe, Patrick (2023)
Natural ventilation systems utilise pressure differentials that arise from wind and buoyancy forces to drive air through buildings. Natural ventilation is typically described using envelope flow models. These are used to size window openings at the design stage, and to predict the annual dynamic thermal performance of buildings. However, envelope flow models rely on highly idealised descriptions of flow through ventilation openings, which do not model realistic window geometries encountered in practice, and assume that ambient air is static. When envelope flow models are applied to building design, inadequate accounting for phenomena relating to wind and opening geometry can lead to under-sized ventilation openings and under-performing buildings.